2019
DOI: 10.1016/j.jlumin.2018.10.067
|View full text |Cite
|
Sign up to set email alerts
|

Lanthanide luminescence sensitization via SnO2 nanoparticle host energy transfer

Abstract: Using a sol-gel synthesis method, nanoparticles of SnO 2 doped by a range of lanthanide ions (Ln 3+) were produced. The UV-visible photoluminescence (PL) emission and excitation spectra were analyzed. Upon excitation of the host oxide at energies above its fundamental bandgap, efficient sensitization of PL emission of all the lanthanide ions was observed. The effects of the Ln 3+ concentrations and ionic radii on the spectra were discussed and interpreted in terms of likely mechanisms of host-guest energy tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…It is worth mentioning here that according to ref , multiple sites exist in the lattice of lanthanide-doped materials, which were studied by the visible emission bands of the Ln 3+ . For example, after investigating the local structure around the Ln 3+ dopants, it was found that Ln 3+ ions enter the ABNbO 3 structure with A and B being alkali and alkaline earth metals not only by substituting A and B but also by substituting Nb lattice positions .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…It is worth mentioning here that according to ref , multiple sites exist in the lattice of lanthanide-doped materials, which were studied by the visible emission bands of the Ln 3+ . For example, after investigating the local structure around the Ln 3+ dopants, it was found that Ln 3+ ions enter the ABNbO 3 structure with A and B being alkali and alkaline earth metals not only by substituting A and B but also by substituting Nb lattice positions .…”
Section: Resultsmentioning
confidence: 99%
“…Depending on which site Ln 3+ ions occupy, different transitions can be achieved. If the active ions occupy the site with C 2 symmetry (RE sites), which leads to the removal of the parity-forbidden f–f transition, a higher intensity can be observed . Magnetic-dipole transitions are independent of site symmetry, whereas electric-dipole ones are only allowed at sites of low symmetry with no inversion center . Therefore, the high intensity of some peaks indicates that a significant proportion of the Pr 3+ is located in noncentrosymmetric sites, whereas broad emission lines are related to the lower incorporation of Pr 3+ ions into the crystal lattice …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations